Efek Kegagalan Alat Flue Gas Desulphur Terhadap Tegangan Lewat Denyar Isolator - Tedy Juliandhy; T. Haryono; Suharyanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Flashover is a disorder condition that occurs in the form of sparks appearing between insulators or electrical component of high voltage. This can occur due to insulation failure of the high voltage system. Failure of insulation in high voltage insulators in Tanjung Jati B substation Jepara is one of the causes of acid rain due to the condensation of smoke from the Tanjung Jati B power plant chimney. Acid rain arises due to failure Flue Gas Desulphur ( FGD ) devices were installed in the plant to reduce gas emissions as a condition of eco-friendly power plant that is planned by the government through the department of Environment . The real action is taken to dismiss the notion that power plant fuel coal is one of the industries that emit SOx and NOx emissions are high on operational processes . The effects of gas emissions is one of the causes of acid rain on the environment . The amount of acidity of acid rain that occurred in the industrial area will always affect the high voltage power lines that distribute power in operation . Sometimes the equipment functions as an insulator in high voltage substations that distribute power at 500 kV network SUTET JAMALI network on the island of Java in a system of operation is interrupted because of pollutants attached to the insulator . Rain with a pH between 4-5 categorized as acid rain and the test affects the time of the flashover voltage drop of 145.5 kV – 142.5 kV of the working voltage , this causes an insulator as insulation materials can be minimized distance insulator surface so that termites can affect the resistance of an insulator in its function as a tool to restrain the occurrence of flashover voltage from voltage parts.